2013
DOI: 10.1007/s00259-013-2514-8
|View full text |Cite
|
Sign up to set email alerts
|

Areas of normal pulmonary parenchyma on HRCT exhibit increased FDG PET signal in IPF patients

Abstract: PurposePatients with idiopathic pulmonary fibrosis (IPF) show increased PET signal at sites of morphological abnormality on high-resolution computed tomography (HRCT). The purpose of this investigation was to investigate the PET signal at sites of normal-appearing lung on HRCT in IPF.MethodsConsecutive IPF patients (22 men, 3 women) were prospectively recruited. The patients underwent 18F-FDG PET/HRCT. The pulmonary imaging findings in the IPF patients were compared to the findings in a control population. Pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 17 publications
6
69
0
Order By: Relevance
“…In addition, increased 18 F-FDG uptake in areas of apparently normal pulmonary parenchyma on HRCT was observed in patients with IPF (16). This finding suggested that higher 18 F-FDG uptake by less-affected lung tissue may provide additional clinical information in patients with ILD, in addition to the morphologic changes observed by HRCT.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, increased 18 F-FDG uptake in areas of apparently normal pulmonary parenchyma on HRCT was observed in patients with IPF (16). This finding suggested that higher 18 F-FDG uptake by less-affected lung tissue may provide additional clinical information in patients with ILD, in addition to the morphologic changes observed by HRCT.…”
mentioning
confidence: 82%
“…SUV mean was measured in 1 target volume of interest (VOI), which was placed at the most normalappearing area in the lungs of each subject. The target VOIs had a fixed spheric shape measuring 18 cm 3 (16). The area occupied by the VOI typically shows no or minimal signs of increased attenuation on CT (Fig.…”
Section: Image Analysismentioning
confidence: 99%
“…Inflammation characterizes several lung diseases, including pneumonia, cystic fibrosis, chronic obstructive pulmonary disease (COPD), acute respiratory distress syndrome (ARDS), asthma, and interstitial lung diseases such as idiopathic pulmonary fibrosis (IPF), among others (7,8,10,11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Because ARDS, COPD, and IPF can cause significant variability in the amounts of air, blood, and water in the lungs (Fig.…”
Section: Clinical Applications Investigated With 18 F-fdg Pet Imagingmentioning
confidence: 99%
“…Glycolytic reprogramming has been shown to play an important role in the pathogenesis of lung fibrosis (7). Recent studies have reported that patients with IPF exhibit higher glycolytic activity in fibrotic areas, with positive retention index values being a strong predictor of deterioration in pulmonary function and of higher mortality (8,9).…”
mentioning
confidence: 99%